Socioeconomic empowerment of women in rural Peru: A cross-sectional study of internal and external determinants in Chepén - Leidy Graciela Carbajal Castillo; Jennifer Nicole Rivas Alvitres; Marco Agustín Arbulú Ballesteros (Economies, 2025)
This study examines the determinant factors of women's empowerment in Chepén, Peru, during 2024, analyzing how socioeconomic status potentially moderates this relationship. Using a quantitative approach with a non-experimental, cross-sectional design, the research surveyed 367 women aged 22-52 years through digital questionnaires employing validated scales. The results revealed that both internal factors (individual and collective psychological competencies) and external factors (economic and cultural conditions) significantly influence female empowerment (β = 0.57, p = 0.049 and β = 0.87, p = 0.039, respectively). Contrary to our hypothesis, socioeconomic status did not significantly moderate these relationships (internal factors socioeconomic level: β = 0.02, p = 0.323; external factors socioeconomic level: β = -0.02, p = 0.584). The models demonstrated strong explanatory power, with internal factors explaining 84.3% and external factors explaining 58.5% of the variance in women's empowerment. The study found moderate levels of autonomy and decision-making (44.8%) and cultural dimensions (43.3%). While 76.1% of participants had higher education, 41.8% earned below PEN 1500, highlighting a significant education-income gap. These findings suggest that psychological competencies and sociocultural environment enhancement are more critical than initial economic conditions for promoting women's empowerment across all socioeconomic strata. The study recommends implementing targeted public policies to improve cultural and economic conditions, establish flexible educational programs, and promote dignified employment opportunities that recognize women's capabilities regardless of socioeconomic background.
Keywords: 330; determining factors; female empowerment; socioeconomic status; rural development; gender equality; psychological competencies; cultural conditions